The Dynamics of Water Quality in Tilapia (Oreochromis niloticus) Ponds at The Local Fish Seed Center (BBIL) West Koya District Muara Tami Jayapura City - Mantayborbir, Vyona; Indrayani, Ervina; Bukit, Elysabeth Anggreini Br. (Jurnal Media Akuakultur Indonesia, 2023)
This research aims to determine the daily dynamics of water quality in tilapia cultivation ponds at the West Koya Local Fish Seed Center (BBIL), Muara Tami District, Jayapura City. This research used two earthen ponds with a size of 25 x 50 m, and a water depth of 30-50 cm, a water volume of 100 L in one pond. Tilapia fish (Oreochromis niloticus) with an average length of 20 cm and weight of 243 grams were used in this study. Feed at a rate of 3% of fish biomass is given three times a day. The water quality parameters observed in this study were water temperature measured using a digital thermometer, dissolved oxygen using a DO meter DO 30N, water acidity using a pH meter, pH-240L, SERA aqua-test kit used to measure ammonia and nitrate. This research shows that the water quality parameters observed are normal according to the needs of tilapia fish. So it can be concluded that the water quality in the tilapia rearing pond at the West Koya Local Fish Seed Center (BBIL), Muara Tami District, Jayapura City is controlled and suitable for the growth and survival of the tilapia (Oreochromis niloticus) being cultivated.